Analysis of Runoff Coefficient Value on Retention Ponds in Flores Island - Krisnayanti, Denik Sri; Bunganaen, Wilhelmus; E. Hangge, Elsy; Munaisyah, Farah; A. Nursyam, Nurul; Khaerudin, Dian Noorvy (Civil and Environmental Science Journal (CIVENSE), 2019)
Flores Island is one of four big islands in NTT province with an area Â±13,540 km divided into 8 districts. The area is included in areas with unequal distribution of rainfall. Therefore, the amount of water availability during the dry season is relatively low then require to attempts of rainwater harvesting. One of the alternatives is by building a retention pond. The important parameter in the calculation of water availability is the value of runoff coefficient. The purpose of this research is to invent the runoff coefficient value of 30 retention ponds in 8 districts of Flores Island. In this study use rainfall data, climatology and technical of retention basin for the analysis of run off coefficient. The analysis method uses the Penman modification for evapotranspiration calculation and method F.J. Mock for discharge calculation. The result in graphical model uses monthly rainfall data and land slope data. Based on the analytical calculation method, the value of run off coefficient for each district in Flores was ranging 0.00 - 0.72. The minimum value of runoff coefficient happened in November was ranging from 0.00 - 0.39, and the maximum value of runoff coefficient happened in January was ranging from 0.48 - 0.72.